Inferring relative sediment fluxes and landscape evolution trends from C, O and clumped isotopes and mineral composition in detrital carbonate - Hagbi, Ravid; Goren, Liran; Eiler, John M.; Ryb, Uri (Earth and planetary science letters, 2024)
•Combined mineral and isotope compositions for carbonate provenance analysis.•Analysis includes clumped isotopes that are sensitive to rock thermal history.•Sediment compositions are consistent with mixing of two endmember sources.•Inverse model predicts compositions of endmember sources and mixing ratios.•Modeled relative sediment fluxes suggest uniform erosion rate across the basin. The Earth's surface undergoes continuous changes due to the redistribution of surface mass through erosion, sediment transport, and deposition. Quantifying these mass fluxes is essential for understanding the patterns and rates of landscape evolution. Established approaches for estimating these fluxes in drainage basins often fail to distinguish among bedrock sources and suffer from transport-related biases. This problem is emphasized in carbonate terrains that typically lack distinct mineral compositions indicative of sediment sources. Here, we develop a novel approach that combines established mineral proxies, together with oxygen, carbon and ‘clumped’ isotope analyses of detrital carbonates, to evaluate the provenance and relative fluxes of sediment in carbonate-dominated drainage systems. The new approach is applied to the Morag catchment in the Hatrurim Syncline, southern Israel, a well-suited and illustrative field case for its large variability in isotope compositions between marine and metamorphosed carbonate rock sources. In this setting, the clumped isotope analysis is a sensitive tool, enabling us to distinguish among potential source units by their thermal history. The analysis reveals that the variations in mineral and isotope compositions of sediment samples collected from various locations in the Morag catchment are consistent with mixing between two end-member carbonate bedrock sources. We developed an inverse mixing model that infers the compositions of these sources and predicts the mixing-ratio based on the measured mineral and isotope compositions from sediment samples. Optimal sources found by the model are consistent with: 1) Marine carbonates; and 2) marine carbonates altered by post-metamorphic re-crystallization. Model-predicted mixing ratios of end member components of the sediment samples correlate with relative exposure areas of relevant source units. This consistency suggests spatially uniform erosion conditions, such that relief is neither created nor destroyed within at least one fluvial response time. Consequently, a prominent increase in steepness across a lithologic and structural boundary at the upper reaches of the catchment is interpreted to reflect a signature of lithology-dependent erodibility, rather than faster erosion of the steeper terrain.